2019
DOI: 10.3389/fmicb.2019.01711
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and Genetic Predictors of Pathogenicity and Virulence in Flavobacterium psychrophilum

Abstract: Flavobacterium psychrophilum causes bacterial cold-water disease (BCWD) in farmed rainbow trout ( Oncorhynchus mykiss ), with the multilocus sequence typing (MLST) clonal complex (CC) CC-ST10 accounting for the majority of outbreaks globally. The development of alternative strategies to antibiotic treatment of BCWD using bacteriophage-based control of F. psychrophilum , or virulence factors as targets for therapy, requires knowledge of the phage-sensitiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
75
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(83 citation statements)
references
References 53 publications
2
75
1
Order By: Relevance
“…The therapeutic potential of phages FpV4 and FPSV-D22 was further emphasized by the fact that their lytic potential against isolate 950106-1/1 were relatively low (>1000-fold less efficient), compared with their infectivity against the FPS-S6 and 160401-1/5N isolates used in the biofilm experiments. 8 Previous studies have indicated that an initial PHR of at least 10 is required for rapid and effective control of F. psychrophilum infections in fish. 7 However, in liquid cultures, such high PHRs select for phage resistance in the bacterial host population, whereas phage-sensitive clones dominate (>99.8%) the regrowing population at lower (≤0.5) PHRs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The therapeutic potential of phages FpV4 and FPSV-D22 was further emphasized by the fact that their lytic potential against isolate 950106-1/1 were relatively low (>1000-fold less efficient), compared with their infectivity against the FPS-S6 and 160401-1/5N isolates used in the biofilm experiments. 8 Previous studies have indicated that an initial PHR of at least 10 is required for rapid and effective control of F. psychrophilum infections in fish. 7 However, in liquid cultures, such high PHRs select for phage resistance in the bacterial host population, whereas phage-sensitive clones dominate (>99.8%) the regrowing population at lower (≤0.5) PHRs.…”
Section: Discussionmentioning
confidence: 99%
“…Also, several virulent F. psychrophilum strains resistant to several broad-range lytic phages, such as FPS-R9 used in this study, have been isolated from BCWD outbreaks. 8 For control of F. psychrophilum in fish farms, the development of phage resistance is maybe an easier issue to overcome since phages are evolving with their hosts in the environment and thus new ones can be isolated, whereas phage-resistant F. psychrophilum clones show significant decrease in fitness and pathogenicity. 24 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Flavobacterium psychrophilum 950106-1/1, a well-characterized Danish strain isolated in 1995 from rainbow trout in a freshwater farm, was selected for the experiments (serotype Fd, virulent) ( Madsen and Dalsgaard, 1999 , 2000 ; Dalsgaard and Madsen, 2000 ; Sundell et al, 2019 ). Flavobacterium psychrophilum FPS-S6, a Swedish strain isolated in 2017 from rainbow trout (serotype Th, virulent), was utilized for the propagation of phage FPSV-D22 since it was the most efficient host for producing high phage titers ( Sundell et al, 2019 ). The bacteria were stored at −80°C in tryptone yeast extract salts medium [TYES: 0.4% tryptone, 0.04% yeast extract, 0.05% CaCl 2 × 2H 2 O, 0.05% MgSO 4 × 7H 2 O (pH 7.2)] ( Holt et al, 1993 ) and glycerol (15–20%).…”
Section: Methodsmentioning
confidence: 99%
“…Bacteriophages FpV4 and FPSV-D22 were used in these experiments ( Supplementary Table 1 ). FpV4 (lytic phage belonging to Podoviridae family, 90 kb genome) was isolated in 2005 from water with feces samples ( Stenholm et al, 2008 ; Castillo and Middelboe, 2016 ) and FPSV-D22 (lytic phage belonging to Siphoviridae family), isolated in 2017 from fish tissue samples collected at Danish freshwater farms of rainbow trout ( Sundell et al, 2019 ). Both phages were characterized to have a broad host range among F. psychrophilum strains [( Stenholm et al, 2008 ; Castillo et al, 2014 ) and unpublished data].…”
Section: Methodsmentioning
confidence: 99%